Recent trends in image processing and pattern recognition : Second International Conference, RTIP2R 2018, Solapur, India, December 21-22, 2018, revised selected papers.: Second International Conference, RTIP2R 2018, Solapur, India, December 21-22, 2018, revised selected papers. Part II ([2019]) - Unknown
No abstract available